The Impact of the Ruble Exchange Rate on Foreign Direct Investment from the EU to Russia in the Period 2014–2020 - Yu. K. Zaytsev (Финансы: теория и практика, 2023)
The purpose of this study is to explain the impact of fluctuations in the exchange rate of the Russian currency on the inflow of FDI from the European Union to the Russian Federation in the period 2014–2020 in order to provide practical recommendations for the development of investment policy and FDI attraction. The author used a threestage methodology, including theoretical, statistical and empirical analyses. The theoretical positions of the influence of the value of the currency on the inflow of various types of FDI into the national economy are determined. It has been established that the increase in the value of the currency has a positive effect on the inflow of FDI and on industries focused on the domestic market of the country. The weakening of the real exchange rate of the ruble generally had a negative impact on FDI inflows into the Russian market. With the fall in the exchange rate, foreign firms targeting the Russian market have reduced their investments. At the same time, export-oriented firms have increased their presence in the form of fixed investment in Russia. Empirical confirmation of theoretical provisions allows using the obtained results when making decisions regarding investment policy and attracting FDI to the national economy.